Choice and performance of governance mechanisms: matching alliance governance to asset type - Hoetker, Glenn; Mellewigt, Thomas (Strategic Management Journal, 2009)
Abstract Formal and relational governance mechanisms are used in strategic alliances to coordinate resources and mitigate the risk of opportunistic behavior. While recent work has shown that these approaches are not mutually exclusive, we understand little about when one approach is superior to the other. Using data on the governance choices and subsequent performance of alliances in the German telecommunications industry, we find that the optimal configuration of formal and relational governance mechanisms depends on the assets involved in an alliance, with formal mechanisms best suited to property‐based assets and relational governance best suited to knowledge‐based assets. Furthermore, a mismatch between governance mechanisms and asset type can harm the performance of the alliance. Our findings contribute to transaction cost economics, the literature on relational governance, and recent work studying their interaction. Copyright © 2009 John Wiley & Sons, Ltd.